Notes on Norwegian marine Amphipoda 11. Ceradocus torelli (Goes, 1866), a new amphipod for Norway - Wim Vader; Niels Krarup Leth (Fauna Norvegica, 1990)
Several specimens of the circumpolar melitid amphipod Ceradocus torelli (Goes, 1866) were found in stomachs of cod Gadus morhua in Stålvikbotn, N. Norway. These are the first records of this large and spectacular amphipod from Norwegian waters.